In the Ensemble with Technical Subjects - V. I. Ignatyev (Дискурс)
Introduction. The purpose of the paper is to test the hypothesis about the entry into the social interactions of actors of a special kind - devices with artificial intelligence. The author proposes to discuss a hypothesis about the emergence of a new species of a subject of artificial nature. The concept is based on the concepts developed by the author of a technosubject and a new kind of subjectivity. The character of a new type of interaction agent is analyzed, its varieties are revealed.Methodology and sources. When identifying signs of similarity between human and machine subjectivity, the author proceeds from interpretations of the subject and subjectivity in the works of G. Tononi, M. DeLanda, G. Deleuze, F. Guattari, S. Beskaravayny. The sources are the studies of T. Walsh, R. Brooks, D. Jordan, D. Markoff, R. Jonck, R. Kurzweil, A. Greenfield, K. Kelly, Sh. Turkle. The results of experiments on the construction of the social community of robots at the Kurchatov Institute and the Institute of Robotics at Carnegie Mellon University, the results of sociological studies of the nature of human relationships with robots carried out by Sherry Turkle from Massachusetts Institute of Technology are taken into account.Results and discussion. It is proved that human interaction with a techno-subject forms a special type of sociality - a hybrid society. The mechanism and features of social interactions in a hybrid type of society are revealed. The specificity of inter-actions arising between a person and various types of techno-subject is revealed. The process of the occurrence and occurrence of human anthropomorphic reactions to the activity of robots is analyzed. There is a transition from copying anthropomorphic features to devices with artificial intelligence to the formation of their subjectivity. The options for constructing human relationships with robots are considered.Conclusion. The conclusion is drawn that there is a high degree of likelihood of an increase in the future conflict between the two lines of improvement of androids based on the creation of a universal humanoid intelligence: strengthening or replacing a person. An alternative possibility of the third direction is considered: harmonization of relations between participants in a hybrid society.